Strategi Dalam Menghafal Al-Qur’an Di Madrasah Tsanawiyah Yapi Sipare-Pare - Nurul Izzah; Rizka Harfiani (Jurnal Penelitian dan Ilmu-Ilmu Keislaman, 2023)
This research is a type of qualitative research using an inductive reasoning research model which aims to find out what strategies teachers use in memorizing the Al-Qur'an students at MTs Yapi Sipare-pare. The research method used in this study is a descriptive qualitative research method to analyze data in the form of sentences or words. Data collection techniques were carried out through observation, in-depth interviews, and documentation. Data were analyzed by data collection, data reduction, data presentation, and data verification. Checking the validity of the data is done by testing the credibility, transferability testing, penguin dependability, and confirmability testing. The results showed that: the strategy carried out by the Tahfidz Teacher at MTs Yapi Sipare-pare in improving students' ability to memorize the Koran, consisted of several actions, namely: 1), giving motivation to students, 2), giving assignments and punishments to students, and 3), guiding students to remain muraja'ah. The obstacles faced by the Tahfidz teacher at MTs Yapi Sipare-pare in an effort to improve students' ability to memorize the Koran, namely as follows: 1), there are students who have not been able to read the Koran properly, 2), the health of the teacher which can interfere with concentration in teaching, 3), there is a feeling of laziness from students when memorizing the Koran, and 4) there is a different intelligence from the students. The solution to this obstacle can be overcome by the teacher by giving tahsin guidance which is carried out periodically. In addition to the presence of several students who have not been able to read the Koran properly, there are also students who are lazy to memorize. This situation does not occur every day, but when students feel lazy, it will be difficult for students to memorize, even for teachers to guide student memorization. The solution that teachers can do to prevent students from feeling lazy is to always provide motivation in the form of advice and continuous memorization targets so that student memorization is always measurable. In addition to these obstacles there are also obstacles that in practice are not in accordance with the theory presented by the author.